POLA PEMBERITAAN TRAGEDI KERUSUHAN SEPAK BOLA DI STADION KANJURUHAN PADA SURAT KABAR JAWA POS (The Commercium, 2023)
The tragedy of the football riot at the Kanjuruhan Stadium, Malang, East Java on October 1 2022 resulted in hundreds of fatalities. From this incident, various media were busy reporting on the tragedy of the riot. One of the mass media that reported on the tragedy at the Kanjuruhan Stadium was the Jawa Pos newspaper. This research is intended to find out the pattern of reporting by the Jawa Pos newspaper regarding the football riot tragedy at the Kanjuruhan Stadium for the period 2 October - 20 November 2022. The author applies an analytical modelframing Zhongdang Pan and Gerald M. Kosicki. This study also uses a constructivism paradigm and a qualitative approach. The results of this study indicate that if a pattern is found used by Jawa Pos in presenting the news on the football riot tragedy at Kanjuruhan Stadium. Based on the syntactic structure in terms of the selection of sources, Jawa Pos uses quotes from various sources. From the structure of the script, the Jawa Pos newspaper tries to tell the news of the football riot tragedy at the Kanjuruhan Stadium using the complete 5W+1H element. But in some news there is an omission of one element. Meanwhile, in the structure of the script, thematically, Jawa Pos tends to make additional subtitles in most of its stories to emphasize an issue that the public wants to convey. Finally, the rhetorical structure, Jawa Pos puts more emphasis on photos. The photo was used by Jawa Pos to validate the issues raised in the news. Apart from that, Jawa Pos also highlighted the negligence of the Arema FC implementing committee and its prominence towards the PSSI Extraordinary Congress (KLB) pressure.